2019
DOI: 10.1111/1759-7714.13250
|View full text |Cite
|
Sign up to set email alerts
|

Clinical manifestation and management of immune checkpoint inhibitor‐associated cardiotoxicity

Abstract: Immune checkpoint inhibitors (ICIs) targeting programmed death-1 (PD-1), its ligand (PD-L1), and cytotoxic T-lymphocyte-associated antigen 4 (CTLA4) have revolutionized cancer treatment by recovering the attack of T lymphocytes on the malignant cells. They have improved clinical outcomes dramatically in multiple types of advanced-stage malignancies. Even though the tolerance and safety profiles are generally good, it has been widely reported that ICIs can cause severe or fatal immune-related adverse events (ir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 25 publications
(38 reference statements)
0
10
0
1
Order By: Relevance
“…ECG abnormalities were reported in 89% of patients diagnosed with ICI-associated myocarditis. ECG findings include Q wave formation, ST-T changes, R wave decrease, QRS widening, and possible various arrhythmias (sinus tachycardia, supraventricular and ventricular premature beats, atrial fibrillation, ventricular tachycardia, and fibrillation) or conduction disturbances (from bundle-branch block to complete atrioventricular block) [ 49 , 71 ]. Atallah-Yunes et al [ 72 ] reported complete atrioventricular block as the most common complication of ICI-related myocarditis.…”
Section: Clinical Manifestation Of Ici-associated Cardiac Toxicitymentioning
confidence: 99%
See 4 more Smart Citations
“…ECG abnormalities were reported in 89% of patients diagnosed with ICI-associated myocarditis. ECG findings include Q wave formation, ST-T changes, R wave decrease, QRS widening, and possible various arrhythmias (sinus tachycardia, supraventricular and ventricular premature beats, atrial fibrillation, ventricular tachycardia, and fibrillation) or conduction disturbances (from bundle-branch block to complete atrioventricular block) [ 49 , 71 ]. Atallah-Yunes et al [ 72 ] reported complete atrioventricular block as the most common complication of ICI-related myocarditis.…”
Section: Clinical Manifestation Of Ici-associated Cardiac Toxicitymentioning
confidence: 99%
“…Laboratory tests (including cardiac troponin and natriuretic peptides) and repetitive ECGs are suggested for the early diagnosis of subclinical cardiotoxicity associated with ICI, combined with prompt access to TTE in doubtful cases [ 43 , 71 ]. At each visit during ICI treatment, the patient should be inquired about cardiac symptoms and a careful physical examination should be performed.…”
Section: Diagnosis Of Ici-associated Cardiotoxicitymentioning
confidence: 99%
See 3 more Smart Citations